Legal Education as Public Policy - Gonzales Mantilla, Gorki (2010)
This paper is about the relationship between the legal formation and its incidence in the sense of the constitutional democracy. It been divided in three axes that, they all included, emphasizes the importance of a legal formation in order to a constitutional democracy. The first axe is about the political character of the legal formation. This permits set in the model of the basic institutional sceneries in the life of the society. Likewise, he points that the law schools act as an authoritative source of the legal culture and over the sense of the law. In this line, he says that the law schools are crucial in the formation of not only lawyers, but also the committed citizens with democracy at the time to take decisions. The second axe is over the law schools along the public policies. The education in the faculties could propitiate the legitimacy of certain rights, interests and liberties that are necessary in the society. Furthermore, it been related with the special situation of the lawyer over the decisions making that requires a major responsibility in the legal practice, which must to be valued in the institutional context. The third axe is about the lawyer profile, the market and the public policies. Nowadays, the legal formation it been based in the legal formalism, as a market demand, that wants to keep the status quo and is unfriendly with the requirements of the constitutional democracy. The author mentions that is necessary a previous university accreditation to establish minimum standards in the legal formation, if not, it would be subordinate the public values to the contingent exigencies of the market. Finally, he says that the lawyer profile must respond in a critical way to the market due to its importance to consolidate the constitutional democracy.